Trade and environment theory and policy in the context of EU enlargement and transition economic - Maxwell, John W., 1964-; Reuveny, Rafael; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2005)
The debate about how best to manage the interplay between trade, industrialization and the impacts of both on the global environment continues to rage, particularly in the context of the introduction and ratification of the Kyoto Protocol. This book deals with a number of important issues surrounding the debate about trade and the environment, but places particular emphasis on the process of EU enlargement.
pt. 1. The trade-environment debate in context : the US decision on Kyoto -- pt. 2. Trade and environmental policies -- pt. 3. Environmental policy concerns in the context of EU enlargement -- pt. 4. Economic and environmental policies in transition economies.
"The papers in this volume have been selected from several papers presented at the Fondazione Eni Enric Matte (FEEM) in Milano, Italy in the summer of 2002 in two workshops on trade, the environment and carbon flows in Europe ... The papers ... have been revised and updated"--Introd.
Includes bibliographical references and index.
Keywords: Free trade -- Environmental aspects -- Europe, Eastern; Free trade -- Environmental aspects -- Europe, Central; Free trade -- Environmental aspects -- European Union countries; Environmental policy -- Europe, Eastern; Environmental policy -- Europe, Central; Environmental policy -- European Union countries; European Union countries -- Economic integration; Electronic books